2016
DOI: 10.1016/j.cognition.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Observing joint action: Coordination creates commitment

Abstract: Previous research has shown that interpersonal coordination enhances pro-social attitudes and behavior. Here, we extend this research by investigating whether the degree of coordination observed in a joint action enhances the perception of individuals' commitment to the joint action. In four experiments, participants viewed videos of joint actions. In the low coordination condition, two agents made independent individual contributions to a joint action. In the high coordination condition, the individual contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

6
4

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 19 publications
8
70
1
Order By: Relevance
“…One possible explanation for why we did not observe a significant difference between coordinating and not coordinating when deciding for joint rewards with a risk-seeking partner is that coordination may have triggered two distinct factors pulling in opposite directions: one the one hand, coordination may have made participants more inclined to choose as they believed the partner wanted (i.e., more risk seeking). This tendency is consistent with research showing that coordination increases a sense of commitment to a partner, increasing the willingness to act in accordance with the expectations one takes that partner to have (Michael, Sebanz & Knoblich, 2016;Rusch & Luetge 2016). On the other hand, coordination may have reduced psychological distance to the partner, leading participants to choose in a more risk-averse fashion.…”
Section: Discussionsupporting
confidence: 87%
“…One possible explanation for why we did not observe a significant difference between coordinating and not coordinating when deciding for joint rewards with a risk-seeking partner is that coordination may have triggered two distinct factors pulling in opposite directions: one the one hand, coordination may have made participants more inclined to choose as they believed the partner wanted (i.e., more risk seeking). This tendency is consistent with research showing that coordination increases a sense of commitment to a partner, increasing the willingness to act in accordance with the expectations one takes that partner to have (Michael, Sebanz & Knoblich, 2016;Rusch & Luetge 2016). On the other hand, coordination may have reduced psychological distance to the partner, leading participants to choose in a more risk-averse fashion.…”
Section: Discussionsupporting
confidence: 87%
“…In support of this hypothesis, Michael, Sebanz & Knoblich (2016) reported evidence that a high degree of spatiotemporal coordination within joint action may function as such a cue, leading agents to remain engaged in the joint action for a longer time and making them Sense of Commitment in HRI 6 more likely to persist until the goal is achieved, while Chennells et al (under review) demonstrated that repeatedly coordinating with the same partner in a decision-making context is sufficient to elicit a sense of commitment, leading agents to resist tempting alternatives and thereby sustaining cooperation through fluctuations in individuals' interests. In a similar vein, Székely & Michael (2018) probed the hypothesis that one's perception of a partner's investment of effort in a joint action may provide such a cue --i.e.…”
Section: Introductionmentioning
confidence: 77%
“…There may be several reasons for why informed participants engaged in communicative modulations despite the informative redundancy. First, the persistent use of communication may have served to confirm the overall functionality of the jointly established communication system and to acknowledge the joint use of the system to the co‐actor, thereby demonstrating the actor's commitment to the joint action (see Michael, Sebanz, & Knoblich, , ).…”
Section: Discussionmentioning
confidence: 99%